(untitled) (Asian Journal of Social Science Studies, 2022)
Minors are the future of every family, society, country, and even all mankind. Among minors, there is a group of minors who have been left unattended for a long time when they are most in need of guardianship because of their parents serving sentences. Such a group with a difficult living condition and an easily neglected situation has naturally become a high incidence of juvenile delinquency. In order to effectively solve the plight of this group, China’s legislative and judicial circles and governments at all levels have tried and explored. This paper explores the relationship between the protection of human rights and crime prevention of this group. At the same time, it reviews the progress in the protection of human rights of this group in recent years and puts forward constructive suggestions.